Immune response to recombinant Leishmania infantum lipophosphoglycan 3 plus CpG oligodeoxynucleotides in BALB/c mice. (March 2017) - Pirdel, L.; Zavaran Hosseini, A.
Summary: Development of a protective antileishmanial vaccine is an urgent priority for successful control of different forms of leishmaniasis. The potential of a recombinant lipophosphoglycan 3 (rLPG3) expressed by Leishmania tarentolae was evaluated in combination with CpG oligodeoxynucleotides (CpG‐ODN) as a Th1‐promoting adjuvant against Leishmania infantum infection in BALB/c mice. First, mice were immunized subcutaneously with rLPG3 either alone or in combination with CpG‐ODN. Next, the immunogenic and protective efficacies of this vaccine were analysed in immunized mice. It was observed that coadministration of rLPG3 with CpG‐ODN led to enhance in a Th1 response to rLPG3 induced by itself as the IFN‐γ production was promoted in association with the predominant presence of IgG2a antibodies in the sera. However, immunization with rLPG3 plus CpG‐ODN induced partial protection against infectious challenge in BALB/c mice. Taken together, further studies are required to improve the protective efficacy using either more potent immune enhancers or vaccination strategies.